You can add or subtract like terms; i.e., like terms are the X^2 or the X or the numbers. Adding we get
2x^2+(-7x^2) = -5x^2
6x+(+2)2x = 8x
1+(-3) = -2
So the answer for the addition is
-5x^2+8x-2
For subtraction you do them this way
2x^2 -(-7x^2) = 2x^2+7x^2 = 9x^2
6x-(+2x) = 6x-2x=4x
etc
add or subtract (2x^2+6x+1)+(-7x^2+2x-3)
5x^2-4x-2
-5x^2+8x-2
5x^2-8x+2
-9x^2-8x+2
(3x^2-7x-4)-(6x^2-6x+1)
-3x^2-x-5
-3x^2-13x+5
9x^2-x+5
3x^2-13x-5
These are just practice problems. could someone help me figure out how to solve them and explain how they got the answer?
@Steve can you help me? or @Reed
3 answers
is this right?
No its right...